The Impact of A Beauty Vlogger's Credibility on Purchase Intention Mediated By Consumer Attitude: The Case of Maybelline New York in Surabaya - Nerissa Idelle (iBuss Management, 2020)
In today’s era, many women in Indonesia watch beauty vlog to know the review or new information about makeup products which become an opportunity for makeup brands to endorse beauty vlogger as their marketing tools. This research examines the impact of a beauty vlogger’s credibility that includes expertise, attractiveness and trustworthiness on purchase intention mediated by consumer attitude in the context of Tasya Farasya and Maybelline New York. The data collection was carried out by distributing questionnaires to women in Surabaya with simple random sampling. The number of respondents gathered is 108 in which the researcher managed to get 100 valid data. Furthermore, the questionnaire result is tested using the classical assumption and multiple linear regression tests. The result indicates that there is a significant influence of credibility to purchase intention mediated by consumer attitude. Keywords: Credibility, Purchase Intention, Consumer Attitude